THE USE OF PEER ASSISTED LEARNING TO INCREASE STUDENTS’ WRITING ABILITY - Aprizawati Aprizawati; Ari Satria (Politeknik Negeri Bengkalis, 2016)
Abstract: The purpose of this research was to investigate whether Peer Assisted Learning (PAL) was effective to increase students’ writing ability in the context of teaching writing for the second year students at SMAN 1 Sungai Pakning. The research was carried out for three months. Students were selected by using cluster sampling. Dealing with the research instrument of collecting the data, some steps were made by using the action research of single cycle; plan, act, observe and reflect. Firstly, to identify the students’ ability in writing narrative text by using PAL, the written test was used consisting of pretest, treatment and posttest. Secondly, observation sheet was prepared which was used to observe directly the students in writing and the influence of PAL (independent variable) toward the students’ ability in writing narrative text (dependent variable). In this case, students who got poor score in pre-test became the writer and students who were good would be the helper. The average score of pretest was 58.21 and the post-test was 78.7. The difference was 20.49. The score of Standard Deviation was 6.84 and the match of t-test was 17.36. The progress of this research showed that the students’ ability improved by using PAL for 20.49 or 60.27%.Keywords: Peer Assisted Learning, Writing, and Narrative.